Surface structure study of imidazolium based ionic liquid - Kadel, Rajesh (Kansas State University, 2008)
Interest in the properties of room-temperature ionic liquids is rapidly expanding. Although there have been numerous studies concerning their preparation, their use as a reaction medium and their physical properties, Ionic Liquids (ILs) are so new that many of their bulk physicochemical properties, optical properties, surface properties, toxicities etc. are unknown or only just beginning to be characterized. The highly polar nature of the ILs causes the surfaces of the liquids to become highly ordered in comparison with the surfaces of many other types of organic liquids. Surface structuring at the liquid-vapor interface of the imidazolium based ILs can be examined by using Brewster Angle Ellipsometry and Contact Angle Measurement. The preliminary observation of Ellipsometric measurement shows that there is an interfacial order-disorder transition at temperature Tc=385 K. This result is not analyzed yet but the initial thought behind this is an indication of a ferroelectric transition at the liquid-vapor interface of dipole moment of ILs. From the contact angle measurement it is shown that there is a remarkable change in the contact angle of the imidazolium based ILs over short interval of time ([similar to] ten minutes). Also study of the spreading of the ILs on hard surface shows that there is some definite structural dependence
Keywords: CM; Physics, Condensed Matter (0611)